Right hemispheric dominance of inhibitory control: an event-related fMRI study. - GARAVAN, HUGH PATRICK (National Academy of Science, 1999)
Normal human behavior and cognition are reliant on a person?s ability to inhibit inappropriate thoughts, impulses, and actions. The temporal and spatial advantages of event-related functional MRI (fMRI) were exploited to identify cortical regions that showed a transient change in fMRI signal after the withholding of a prepotent motor response. The temporal specificity of the event-related fMRI design also minimized possible contamination from response inhibition errors (i. e., commission errors) and other extraneous processes. Regions identified were strongly lateralized to the right hemisphere and included the middle and inferior frontal gyri, frontal limbic area, anterior insula, and inferior parietal lobe. Contrary to the prominence traditionally given to ventral frontal regions for response inhibition, the results suggest that response inhibition is accomplished by a distributed cortical network.
PUBLISHED
Keywords: Psychology